Difference Curing Conditions on the Engineering Properties of High Strength Lightweight Reinforced Concrete (HSLRC) using Sawdust and Coconut Fiber - Zakaria, Noor Zawati; Sulieman, Mohd Zailan (International Journal of Sustainable Construction Engineering and Technology, 2020)
This paper studies the effect of different curing conditions using sawdust and coconut fiber as partial fine aggregate replacement in high strength lightweight reinforced concrete (HSLRC). The concrete mix ratio 1:3 was prepared using water-cement ratio of 0.35 with level of 0%, 20%, 35%, 50%, 65% and 80% of sawdust and 3% coconut fiber as reinforcement in air environment (A-series) and water curing (W-series) were evaluated in terms of engineering properties i.e., compressive strength, flexural strength, water absorption ,and density. The test results showed that concrete density and compressive strength values decreased while water absorption increased with the increase in sawdust and coconut fiber percentages. However, the strength obtained at HSLRC-50 has met the minimum specified requirement of 40 N/mm2 for normal concrete. Thus, the results showed A-series most reliable correlation coefficient (R2) value between these variable parameters compared to water curing W-series. It can be concluded that the air environment curing affected the relationship between variable parameters for long-term exposure days. Using with and without sawdust and coconut fiber can be used as a construction material with acceptable strength and density properties of concrete mix.